Persepsi Guru dan Adaptasi Terhadap Perubahan Kurikulum - Marlina, Marlina; Qomarudin, Muslih; Sholeh Hasan; Tasdiq, Tasdiq; Yovillia, Yovillia (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
This study explores teachers' perceptions and efforts to adapt to curriculum changes in the educational context. Utilizing a quantitative approach, the research employs the method of percentage descriptive analysis. The research sample consists of 20 randomly selected teachers using the Slovin formula. The analysis results indicate that 70% of teachers' perceptions fall into the moderate category, reflecting a positive response to the independent curriculum, while 65% have successfully adapted to the curriculum changes. The implications of these findings can guide policymakers and educational institutions in enhancing the implementation of curriculum changes. This research significantly contributes to understanding the dynamics of teachers' perceptions and their adaptation processes in the face of educational system changes, emphasizing the importance of supporting teachers to improve the quality of education.